Evaluation of the catalytic effect of potassium tungstate in green decontamination for detoxification of 2-chloroethyl phenylsulfide (2-CEPS) - Vu Thanh Binh; Nguyen Thanh Hoa; Do Ngoc Khue; Nguyen Khanh Hung; Dao Duy Hung (Тонкие химические технологии)
Objectives. 2-Chloroethyl phenylsulfide (2-CEPS) is a relevant simulant of chemical warfare sulfur mustard gas (yperit) as part of an environmentally-friendly decontamination processes. This study presents the initial results of research the catalytic ability of tungstate in the conversion process of 2-CEPS.   Methods. The decontamination system employed in this study comprised hydrogen peroxide (H2O2), potassium tungstate acting as a metal transition salt catalyst, a surfactant, and organic solvents. The research investigated the impact of K2WO4 concentration on the conversion efficiency and rate of the target compound. As well as additionally exploring the influence of the substrate-to-catalyst ratio on the reaction pathway, the study evaluated the stability of the detoxifying mixture.   Results. Increasing the concentration of K2WO4 is shown to lead to an increase in the efficiency and conversion rate of 2-CEPS. As well as demonstrating stability and durability, the catalyst did not cause unwanted H2O2 breakdown. After 18 h of mixing, the conversion retained efficiency above 95 % within 15 min of the reaction. The degradation kinetics follow a pseudo-first-order model, indicating that the reaction rate is directly influenced by the K2WO4 concentration. In addition to enhancing the oxidative capacity of the solution, increased tungstate concentration promotes the formation of undesirable sulfone byproducts.   Conclusions. The study investigated the catalytic activity of tungstate within an eco-friendly solution formulated to degrade 2-CEPS. Our findings demonstrate a strong correlation between the concentration of potassium tungstate (K2WO4) and the rate of 2-CEPS degradation. A key advantage of tungstate is its exceptional stability and durability as a catalyst. Efficient decontamination is ensured thanks to its minimal interference with the stability of hydrogen peroxide (H2O2).